Tras los pasos del Interregionalismo MERCOSUR-ASEAN: el Acuerdo de Libre Comercio con Singapur y su dinámica comercial - Fernandez Guillen, Oscar Eduardo (2024)
This article analyses the MERCOSUR-Singapore Free Trade Agreement's negotiation process and explains the dynamics and intensity of inter-regional trade relations from 2001 to 2023. To this aim, the study employed empirical research, supported by qualitative and quantitative methods. Based on the documentary review and the calculation of trade indicators, it concludes, among other things, that the MERCOSUR-Singapore Free Trade Agreement is a milestone within MERCOSUR-ASEAN inter-regionalism, achieved by Paraguay's leadership in the negotiations, and that bilateral exchanges with Brazil determine both the current position and the dynamics and intensity of MERCOSUR-Singapore trade.